2019
DOI: 10.3389/fphys.2019.00608
|View full text |Cite
|
Sign up to set email alerts
|

Increased Expression of lncRNA UCA1 and HULC Is Required for Pro-inflammatory Response During LPS Induced Sepsis in Endothelial Cells

Abstract: Systemic uncontrolled inflammatory response, also termed as sepsis, is responsible for many mortalities. Bacterial endotoxin, lipopolysaccharide (LPS), is a major cause of sepsis in endothelial cells. Even though a lot of research has been done to define underlying mechanisms of LPS induced sepsis, the role of long non-coding RNAs (lncRNAs), a group of >200 kb RNAs in sepsis is not well-defined. Expression of pro-inflammatory mediators IL6, ICAM1, and VCAM1 (which encodes interleukin-6, intercellular adhesion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
59
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(62 citation statements)
references
References 23 publications
3
59
0
Order By: Relevance
“…The Long non-coding RNA UCA1 was located in chromosome 9p13.12, and has been found to be overexpressed in tumor tissues, such as esophageal squamous cell carcinoma,colorectal cancer, ovarian cancer, bile duct carcinoma and melanoma etc. [16][17][18][19][20][21][22][23].UCA1 are participated in the tumorigenesis and progression, functioning as an oncogene [24][25][26][27][28][29][30]. However, the relation between UCA1 and renal cancer is still unknown and mysterious particularly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Long non-coding RNA UCA1 was located in chromosome 9p13.12, and has been found to be overexpressed in tumor tissues, such as esophageal squamous cell carcinoma,colorectal cancer, ovarian cancer, bile duct carcinoma and melanoma etc. [16][17][18][19][20][21][22][23].UCA1 are participated in the tumorigenesis and progression, functioning as an oncogene [24][25][26][27][28][29][30]. However, the relation between UCA1 and renal cancer is still unknown and mysterious particularly.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidences suggested that long non-coding RNAs (lncRNAs) perform important or vital functions in the malignant tumors [9][10][11][12][13][14][15]. LncRNA urothelial cancer associated 1 (UCA1) is abnormally expressed in esophageal squamous cell carcinoma, colorectal cancer, gastric cancer melanoma cells, pancreatic cancer, thyroid cancer, lung cancer and so on [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. In vitro and in vivo assays were conducted to further explore its underlying roles in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al (8) reported that lncrna nuclear paraspeckle assembly transcript 1 (neaT1) knockdown could ameliorate sepsis-induced myocardial damage in mice, including the decrease of edema in myocardial tissues in mice, as well as the inhibition of apoptosis and inflammation. Previous literature has suggested that lncrna highly upregulated in liver cancer (Hulc) was involved in the decrease of pre-inflammatory mediators in lipopolysaccharide (lPS)-induced sepsis in vitro (9). nevertheless, the mechanism of action of Hulc in lPS-induced sepsis remains to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…CRNDE, an oncogene that is usually overexpressed in tumor cells, contributes a lot to cellular proliferation, migration, invasion, and apoptosis [40]. More importantly, CRNDE can modulate the TLR3-NF-κB cytokine signaling pathway to trigger inflammation [41,42], suggesting that CRNDE may serve as a regulator in sepsis. In sepsis, genes or gene modules inducted by MALAT1 may modulate their expression pattern in endothelial cells, which is critical as MALAT1 has been reported to mediate inflammation in traumatic brain injury [42].…”
Section: Validation Using Independent Lncrna Datasetsmentioning
confidence: 99%
“…More importantly, CRNDE can modulate the TLR3-NF-κB cytokine signaling pathway to trigger inflammation [41,42], suggesting that CRNDE may serve as a regulator in sepsis. In sepsis, genes or gene modules inducted by MALAT1 may modulate their expression pattern in endothelial cells, which is critical as MALAT1 has been reported to mediate inflammation in traumatic brain injury [42]. Also, it was reported that TUG1 is able to affect the development of sepsis-associated acute kidney injury via modulating NF-κB pathway [43].…”
Section: Validation Using Independent Lncrna Datasetsmentioning
confidence: 99%